An Improved Phenotyping Protocol for Panama Disease in Banana - García-Bastidas, Fernando A.; Van der Veen, Alexander J. T.; Nakasato-Tagami, Giuliana; Meijer, Harold J. G.; Arango-Isaza, Rafael E.; Kema, Gert H. J. (Frontiers in Plant Science, 2019)
Fusarium oxysporum (Fo) belongs to a group of soil-borne hyphomycetes that are taxonomically collated in the Fusarium oxysporum Species Complex (FOSC). Hitherto, those infecting bananas were placed in the forma specialis cubense (Foc). Recently, however, these genetically different Foc lineages were recognized as new Fusarium spp. placed in the Fusarium of Banana Complex (FOBC). A member of this complex F. odoratissimum II-5 that uniquely comprises the so-called Tropical Race 4 (TR4), is a major problem sweeping through production zones of Cavendish banana in several regions of the world. Because of this, there is an urgent need for a phenotyping method that allows the screening for resistance to TR4 of large numbers of banana genotypes. Most Fusarium species produce three types of spores: macroconidia, microconidia and the persistent chlamydospores that can contaminate soils for many years. Inoculum production has been an important bottleneck for efficient phenotyping due to the low or variable number of conidia and the elaborate laboratory procedures requiring specific infrastructure. Here, we report a rapid, simple and high-yielding spore production method for nine F. oxysporum formae speciales as well as the biocontrol species Fo47 and Fo618-12. For Fusarium spp. causing Fusarium wilt or Panama disease of banana, we used the protocol for four species comprising the recognized physiological races, including Tropical Race 4 (TR4). We subsequently tested the produced inoculum in comparative inoculation trials on banana plants to evaluate their efficiency. All assays resulted in typical symptoms within 10 weeks; significant differences in final disease ratings were observed, depending on inoculum concentration. Pouring inoculum directly onto banana plants showed the most consistent and reproducible results, as expressed in external wilting, internal discoloration and determined by real-time PCR assays on entire rhizomes. Moreover, this method allows the inoculation of 250 plants per hour by one individual thereby facilitating the phenotyping of large mutant and breeding populations.